PENGARUH KEPEMIMPINAN, MOTIVASI, KEPUASAN DAN KOMITMEN TERHDAP KINERJA PEGAWAI PENGADILAN AGAMA WILAYAH PROVINSI BANTEN - Sutoro, Moh.; Sahroni, Mr (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
The implementation of effective and efficient governance is a demand in the era of globalization. This reality demands the professionalism of human resources in realizing good governance. Therefore, various bureaucratic changes were carried out in order to organize a clean government, including developing HR. The purpose of this study was to find, describe, and analyze the influence of leadership, work motivation, job satisfaction and work commitment on employees performance of Religious Courts in Banten Province. This study uses a quantitative method, the research sample is administrative ASN in the Religious Court of Banten Province which amounts to 100 respondents, the sampling technique uses proportional random sampling, the research instrument uses questionnaire and the analysis method uses Multiple Linear Regression with the analysis stage consisting of descriptive analysis, test validity, reliability test, classic assumption test, partial test, simultaneous test and coefficient of determination test. The results showed that leadership, work motivation, job satisfaction and work commitment both partially and simultaneously had positive and significant effect on performance.